The MBA Factor: A Study of Progression - Galbraith, Diane; Mondal, Sunita (Archives of Business Research, 2017)
Many students are flocking to business schools for more advanced degrees than in any other concentration. In what some call, a one to two-year hiatus, these students are trying to reverse the recent trend of a downwardly mobile generation with fewer opportunities and more accumulated debt. Master of Business Administration graduates are seeking a better future, upward mobility and satisfying jobs upon graduation. A 2015 Bloomberg study of the best business schools reveals that 88% are hired within 3 months of graduation, with a substantial jump of up to 81% in compensation before school. This study utilizes survey data to follow the graduates of a Mid-Atlantic University as their careers progress after graduation to determine whether there is a tangible return on their educational investment and an increase in their respective skill development. Results confirm the usefulness of the MBA degree in career progression.